Advice giving and the management of uncertainty for cancer survivors: An exploratory study. - Thompson, Sharlene R. (My University, 2005)
Previous research on advice in supportive interactions has focused exclusively on facework, advice content, and receptivity to advice and has not systematically considered the effects of uncertainty management processes, information sensitivity and advice optimism. Further, this research examines advice and uncertainty management in the context of cancer survivorship. The current study examines the relative influence of target receptiveness, information sensitivity, advice content and advice optimism on uncertainty management processes, emotion coping processes, problem coping processes and advice evaluation. Participants (N=161) completed a questionnaire (online or paper) reporting on informal advice received after diagnosis. Results indicated that target receptiveness and advice optimism were positively related to problem coping processes. Target receptiveness, advice optimism and absence of limitations were positively related to emotion coping processes. Limitations of the study are offered and implications for future research are advanced in the area of cancer survivorship.
Keywords: Cancer Patients Counseling.; Speech Communication.; Health counseling.